2011
DOI: 10.1002/bsl.1000
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Assessment, Stability, and Correlates to Bullying Roles in Middle School Children

Abstract: The current study investigated bullying behaviors in 284 school children in the fourth through seventh grades at the time of the initial assessment. Peer ratings of bullying behavior were obtained at the end of the spring semester of one school year and at the end of the fall semester of the next school year. Importantly, peer ratings were obtained by assessing not only the level at which participants actually bully other students but also whether participants help bullies to hurt the victim (assister), encour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 57 publications
7
40
0
4
Order By: Relevance
“…Neither can we omit mentioning that all the students were on the same academic level, as the results could be different at other educational levels, since the prevalence of antisocial behavior changes with age (Inglés et al, 2009). It might also have been of interest, and we leave this goal for future research, to analyze the differences by gender, since there are studies which also show its influence (Crapanzano et al, 2011). Nevertheless, this study's contribution should be highlighted, because it shows the values to be worked on and detected for early and preventive intervention in student behavior (antisocial and delinquent) and social attitudes.…”
Section: Discussionmentioning
confidence: 99%
“…Neither can we omit mentioning that all the students were on the same academic level, as the results could be different at other educational levels, since the prevalence of antisocial behavior changes with age (Inglés et al, 2009). It might also have been of interest, and we leave this goal for future research, to analyze the differences by gender, since there are studies which also show its influence (Crapanzano et al, 2011). Nevertheless, this study's contribution should be highlighted, because it shows the values to be worked on and detected for early and preventive intervention in student behavior (antisocial and delinquent) and social attitudes.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies focused on trajectories of bullying within one bullying role. Crapanzano, Frick, Childs, and Terranova () found that perpetration at one time point was highly related to perpetration 7 months later. Espelage, Van Ryzin, and Holt () showed that the most common trajectory of perpetration from age 11 to age 16 was low and moderate, relatively stable across time.…”
Section: Stability and Transitions In Bullying Roles: Existing Theorementioning
confidence: 99%
“…Defending a victim is a form of prosocial behavior. It has been found that children who defend victims also display other prosocial behavior, such as helping and cooperation (Crapanzano, Frick, Childs, & Terranova, 2011). It is interesting to examine whether defenders are more prosocial than outsiders.…”
Section: Behavioral and Peer-valued Characteristics Associated With Pmentioning
confidence: 99%